In Vitro Anti-proliferative Properties of Flavonoids Isolated from Artocarpus Heterophyllus on Cancer Cell Lines - Mat Daud, Nik Nurul N. N.; Abu Bakar, Noor A.; Septama, Abdi Wira (Natural Products Journal, The, 2021)
Artocarpus heterophyllus has been used as a folk medicine. This plant contained a wide range of flavonoid compounds and possessed several pharmacological properties including anticancer properties. Chemotherapeutic agent is a major option for cancer treatment. However, it may lead to tumor relapse. Therefore, it needs to discover an alternative to reduce this limitation using natural products. Objective: This study was aimed to determine anti-proliferative activities of isolated compounds against cancer cell lines. The morphological changes of cancer cell lines after treatment with the compounds was also evaluated. Methods: The flavonoid compounds were determined for their cytotoxic activity against leukaemia HL-60 (CCL-240), colorectal adenocarcinoma HT-29 (HTB-38), breast adenocarcinoma cancer MCF-7 (HTB-22), and non-small lung cancer H460 (HTB-177) cell lines using MTT assay. Hoechst 33342/PI staining assay was used to evaluate the morphological changes, and observed using a fluorescent microscope. Results: It showed that amongst compound, artocarpin consistently exhibited strong cytotoxic activity against H460, HT-29, MCF-7, and HL-60 cancer cell lines with IC50 values of 5.07, 5.56, 12.53, and 19.94 μg/mL, respectively. The activity was comparable to the cisplatin as a positive control. Morphological observations showed the most typical apoptotic morphology of cancer cells upon treatment with artocarpin and the least typical of apoptotic structure with other compounds. Conclusion: It can be suggested that A. heterophyllus bioactive compound modulates apoptosis by the presence of its distinctive, typical forms of morphological changes in treating cancer cells. Thus, artocarpin compound may provide high potential therapeutic use in chemotherapeutic strategies.
Keywords: Artocarpin